Sensory perception and kinetic relationship with Accuracy and the performance of the skills of handling and scoring football - Dr. Nassar Ismaeil M. Waleed Khalid (physical education and sport sciences college for women/ Baghdad University, 2020)
The mental abilities, such as sensory perception of the motor contribute to the basic skills of the game of football, to meet the different conditions of the game and overcome them to make the right decision at the maximum speed, the performance in the game requires the need for a range of abilities that interfere with each other and sensory perception as one of these requirements, The two researchers called for conducting a study to identify the relationship between sensory perception and the skill of scoring and handling skills of football. The researchers used the descriptive method in the survey method to reach the results of the study. The results of the study revealed a significant correlation between Rak sensory motor skill scoring and handling football skill.